TOXICITY OF MINING DRILLING SLUDGE IN THE PORCELLIO LAEVIS (LATREILLE, 1804) (CRUSTACEA: ISOPODA) BIOINDICATOR - Bautista-Medina, Yadira Blanca (2020)
The toxicity of mining drilling mud was evaluated based on the lethal effect and evasion in the terrestrial bioindicator Porcellio laevis (Latreille, 1804). The following treatments were considered: drilling mud, suspended phase of drilling mud and mining drilling fluid in acute toxicity tests and short evasion test. Toxicity tests did not show a lethal effect in drilling mud, in the suspended phase of drilling mud, and in mineral drilling fluid in P. laevis. In the evasion tests, considering uncontrolled humidity conditions, it was observed that there was a preference for P. laevis towards the land with the presence of drilling mud. However, considering controlled humidity conditions, the preference of P. laevis towards the muddy land was confirmed. The results of this investigation allow documenting a protocol to evaluate the toxicity of mining drilling muds and serve as a reference for future investigations in Peru. Key words: Porcellio laevis – toxicity – drilling mud – evasion test